2009
DOI: 10.1126/science.1178120
|View full text |Cite
|
Sign up to set email alerts
|

Oceanic Spawning Migration of the European Eel ( Anguilla anguilla )

Abstract: European eels (Anguilla anguilla) undertake a approximately 5000-kilometer (km) spawning migration from Europe to the Sargasso Sea. The larvae are transported back to European waters by the Gulf Stream and North Atlantic Drift. However, details of the spawning migration remain unknown because tracking eels in the Atlantic Ocean has, so far, eluded study. Recent advances in satellite tracking enable investigation of migratory behavior of large ocean-dwelling animals. However, sizes of available tags have preclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
286
3
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(312 citation statements)
references
References 5 publications
17
286
3
1
Order By: Relevance
“…However, van Ginneken et al (2005b) and Palstra and van den Thillart (2010) estimated that about 20 % of the energy consumed for swimming is produced from proteins. Considering the fact that eel are known to be much more effective swimmers than thought before (van Ginneken et al 2005b;Palstra and van den Thillart 2010;Clevestam et al 2011), and they save considerable amounts of energy when swimming to the spawning ground and that they swim (at least initially) at water temperatures considerably lower than those at which metabolic studies have been conducted (Aarestrup et al 2009), it may be accepted that energy saving for swimming can be even more effective than originally assumed. It is all the more so that, as these studies have shown, eel usually make use of sea currents rather than swimming upstream.…”
Section: Discussionmentioning
confidence: 99%
“…However, van Ginneken et al (2005b) and Palstra and van den Thillart (2010) estimated that about 20 % of the energy consumed for swimming is produced from proteins. Considering the fact that eel are known to be much more effective swimmers than thought before (van Ginneken et al 2005b;Palstra and van den Thillart 2010;Clevestam et al 2011), and they save considerable amounts of energy when swimming to the spawning ground and that they swim (at least initially) at water temperatures considerably lower than those at which metabolic studies have been conducted (Aarestrup et al 2009), it may be accepted that energy saving for swimming can be even more effective than originally assumed. It is all the more so that, as these studies have shown, eel usually make use of sea currents rather than swimming upstream.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, cross-habitat fluxes of organisms (mediated by passive transport or active migration) occur between natural habitats and across natural/anthropogenic systems, at various geographical scales (5)(6)(7)(8)(9). In heterogeneous landscapes, a particular case of cross-habitat fluxes is represented by source-sink dynamics in which a population from a productive source habitat maintains by migration populations in sink habitats where local reproduction is insufficient to compensate for mortality (10,11).…”
mentioning
confidence: 99%
“…Hence, this technology provides information on the fish position at pop-up time, and stored light, temperature and depth data can be used to calculate fish movements between tagging and the pop-up location (see below). PSATs are relatively large and have to be attached externally, which limits size and species of fish that can be tagged, although some PSATs are now small enough to be used on European silver eel (Anguilla anguilla) (Aarestrup et al, 2009) and adult Atlantic salmon (Chittenden et al, 2013b). The advantage with these tags is that they do not need to be recovered to retrieve data, data is also retrieved from fish that dies (which is often as important as getting data from only those surviving), and an accurate pop-up location is achieved.…”
Section: Pop-up Satellite Archival Tags (Psat)mentioning
confidence: 99%